Botrytis cinerea causes different plant responses in grape (Vitis vinifera) berries during noble and grey rot: diverse metabolism versus simple defence - Váczy, Kálmán Z.; Otto, Margot; Gomba-Tóth, Adrienn; Geiger, Adrienn; Golen, Richárd; Hegyi-Kaló, Júlia; Cels, Thomas; Geml, József; Zsófi, Zsolt; Hegyi, Ádám István (Frontiers in Plant Science, 2024)
The complexity of the interaction between the necrotrophic pathogen Botrytis cinerea and grape berries (Vitis vinifera spp.) can result in the formation of either the preferred noble rot (NR) or the loss-making grey rot (GR), depending on the prevailing climatic conditions. In this study, we focus on the functional gene set of V. vinifera by performing multidimensional scaling followed by differential expression and enrichment analyses. The aim of this study is to identify the differences in gene expression between grape berries in the phases of grey rot, noble rot, and developing rot (DR, in its early stages) phases. The grapevine transcriptome at the NR phase was found to exhibit significant differences from that at the DR and GR stages, which displayed strong similarities. Similarly, several plant defence-related pathways, including plant-pathogen interactions as hypersensitive plant responses were found to be enriched. The results of the analyses identified a potential plant stress response pathway (SGT1 activated hypersensitive response) that was found to be upregulated in the GR berry but downregulated in the NR berry. The study revealed a decrease in defence-related in V. vinifera genes during the NR stages, with a high degree of variability in functions, particularly in enriched pathways. This indicates that the plant is not actively defending itself against Botrytis cinerea, which is otherwise present on its surface with high biomass. This discrepancy underscores the notion that during the NR phase, the grapevine and the pathogenic fungi interact in a state of equilibrium. Conversely the initial stages of botrytis infection manifest as a virulent fungus-plant interaction, irrespective of whether the outcome is grey or noble rot.